Pengaruh Literasi Digital Terhadap Etika Komunikasi Di Media Sosial Pada Siswa SMAN 1 Sungai Mandau - Riki Hendri Hidayat; Indrawati Indrawati (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The development of information technology has changed social communication patterns, especially among students. Social media has become the primary medium for interaction, but this is not always accompanied by ethical awareness among its users. This research aims to analyze the influence of digital literacy on communication ethics on social media among students of SMAN 1 Sungai Mandau. The approach used is descriptive quantitative. A sample of 140 students was taken. Data were collected through questionnaires and analyzed using simple linear regression. The results show that digital literacy has a positive and significant effect on students' communication ethics. Symbolic interactionism theory is used to understand how ethical meanings are formed through symbols and digital social interactions. These findings emphasize the importance of integrating digital literacy education in character development and the communication ethics of students.